2002
DOI: 10.1097/00002820-200212000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Solving Family-related Barriers to Truthfulness in Cases of Terminal Cancer in Taiwan

Abstract: The study investigated the puzzling factors and solutions of family-related barriers to truthfulness with patients with terminal cancer through a nationwide survey conducted in Taiwan. Two-hundred twenty-nine valid questionnaires were retrieved (91.6%) from 250 palliative care workers at 15 Taiwan hospices. Most of the respondents were nursing staff (72.5%), and only 38 respondents were physicians (16.6%). Canonical correlation analysis was used to examine the association between the puzzling factors and solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 17 publications
7
38
0
Order By: Relevance
“…These, in our mind, should include healthy communication with the relatives and being aware of the different types of responses when bad news is received, in accordance with previous studies [6,19]. It has also been shown that such a healthy communication with the relatives would also increase family satisfaction with cancer care [20,21].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These, in our mind, should include healthy communication with the relatives and being aware of the different types of responses when bad news is received, in accordance with previous studies [6,19]. It has also been shown that such a healthy communication with the relatives would also increase family satisfaction with cancer care [20,21].…”
Section: Discussionsupporting
confidence: 72%
“…Most of the relatives (57% of those who did not want disclosure) thought that "the patient will be emotionally worse if he/she knows" and that was the major reason for their opposition to honest disclosure. This kind of thinking may be even more frequently encountered in some other countries [6]. However, we feel that part of this paternalistic attitude of the relatives may also stem from religious belief.…”
Section: Discussionmentioning
confidence: 78%
“…Because of the traditions of Eastern culture, family and physician paternalism are ingrained and prevail in Taiwan's society. Hu et al (2002) found medical professionals here too more often followed patients' family members' opinions rather than those of the patients. These researchers found family-related barriers in telling the truth were that families (1) do not know how to tell the truth (85%); (2) believe it is unnecessary to tell aged patients the truth (71%); and (3) believe patients can be happier without knowing the truth (70%).…”
Section: Cultural Considerationsmentioning
confidence: 98%
“…From our past experience, these 12 principles-including self-acknowledgment of terminal condition, control, dignity, pain and symptom relief, access to appropriate care, timeliness, location, and emotional and spiritual support-correlated with good death in our hospice patients. Moreover, previous studies in Taiwan have identified that awareness of terminal illness [12], fear of death [29], and symptoms control [3] are highly associated with well-being of terminal patients. Taking into account the 12 good-death principles and the findings of previous studies in Taiwan, a pool of good-death items was generated independently by members of the research team to assess the quality of dying in terminal cancer patients.…”
Section: Instrument Developmentmentioning
confidence: 99%